Intonational strategies in ensemble singing - Bohrer, Jocelei Cirilo Soares (2002)
The aim of the research was to find out about intonational strategies in the performance situation. The singing voice was chosen as the appropriate subject for experimental work, due to its superior capability to define pitch as compared to other musical instruments. Ensemble singing was also required, as harmonic context may be important in the clarification of the issue. Chapter One, as an introduction to the subject, considers tuning systems and temperaments and briefly reviews the experimental literature on the subject. It also states the aim of the research. Chapter Two focuses on the theoretical aspects of the research, considering some relevant phenomena of psychoacoustics to the legacy of tuning systems and temperaments. Some thoughts on intonational strategies, reference frequencies and flexible temperament as desirable components of a sound intonational strategy are elaborated. An analysis of the motet Ave Verum Corpus, by Mozart, as the chosen music piece for experimental work is carried out. Chapter Three deals with the delineation of experimental procedures for the evaluation of the intonational strategies adopted by singers in the performance situation. The recording sessions environment and the technical tools utilised in the experiments are described, as well as the technical procedures to carry out the measurements of the acquired data. As strict criteria had to be met regarding the performance situation, simultaneity of performance and the need to acquire individual data for analytical work, electrodes were attached to the neck of the singers, near the larynx, in order to carry out the recording sessions with the help of Laryngograph devices. Analytical issues are also considered in the chapter, namely technical problems, errors and mistakes, as well as the implementation of intonational analyses and reference frequency calculations. Chapter Four presents a discussion on data measurements procedures, including guidelines for the determination of errors and mistakes and their symbology. Four recording sessions were carried out; two of them fulfilled all the necessary requirements. The singers’ results are presented in chronological order: firstly, a quartet of singers from the Royal Academy of Music, and secondly, sixteen of the BBC Singers. Reference frequency results are also presented and discussed. Chapter Five deals with the intonational strategies as defined by the experimental work. It was discovered that no theoretical model was followed throughout the music piece, but instead intonational procedures were guiding the singers while performing. Also, the two groups adopted different intonational strategies regarding reference frequencies. Alongside with the main issues of the research – intonational strategies regarding pitch behaviour and reference frequencies, pitch equalization within a choir section and text-related issues rank amongst the most important topics that have been revealed by the results. Chapter Six comments on the new concepts brought about by the research. It also delineates some possibilities for future research work on the subject and related issues, especially vibrato singing, text articulation and absolute pitch. The Appendices contain images of the experimental work, diagrams of studio disposition for recording sessions, and analytical scores alongside with tuning tables that make it possible to represent graphically analytical values. They also provide means of performing acoustical replications of the results of analysis and singers. The core of the appendices volume is formed by the results of the singers’ fundamental frequencies results and their graphical representation.